Service and Service Systems - Hunter-Jones, Philippa (Business Expert Press, 2014)
Ebook from IG Library ; Unsettled times can arise from a variety of causes, including ones that are environmental, climatic, economic, social or political in nature. They can result in citizens' loss of homes and possessions, jobs, health or mobility. Citizens move from above the level of consumption adequacy, where their behaviors reflect long-term and higher-order needs, to below the level of consumption adequacy, where they are forced into a short-term focus on simple existence.Unsettled times can arise from a variety of causes, including ones that are environmental, climatic, economic, social or political in nature. They can result in citizens' loss of homes and possessions, jobs, health or mobility. Citizens move from above the level of consumption adequacy, where their behaviors reflect long-term and higher-order needs, to below the level of consumption adequacy, where they are forced into a short-term focus on simple existence. In parallel, services provided by various organizations - utilities, transportation, medical, maintenance, housing, education, broadcasting, national state and local governments - may become ineffective or unavailable under such conditions. This book explores the effect of unsettled times on spatial service systems. It describes the scope and breadth of the problem as well as providing solutions by offering original insights from managers of service organizations (especially public services), policy-makers and service system researchers and students. The book briefly introduces the related concepts of consumption adequacy and spatial service systems. The impact of these issues for spatial service systems is analyzed, implications discussed, the lessons to be learned and conclusions will be drawn on the actions needed to build spatial service system resilience for future occurrences. The potential for this book is interdisciplinary, and could be relevant not only for business/management courses, but also in the areas of public administration and also economic geography.